Taguchi Method for Tribological Excellence: Insights into Copper-Based Metal Matrix Composites - S.S. Kallesh; Rajaneesh N. Marigoudar (Tribology in Industry)
Copper matrix composites are widely used in brakes and bearings due to their excellent mechanical properties, wear resistance, and thermal management. This study examines the dry sliding wear of copper matrix composites reinforced with silicon carbide (SiC) particles, produced via powder metallurgy. Optimization of the tribological behavior was conducted via the Taguchi technique and ANOVA were used to analyze wear loss. Confirmation tests were conducted to validate the experimental results. Examined samples were analyzed using a scanning electron microscope. Regression model for predicting wear loss was developed using the Taguchi technique. The influence of SiC loading and tribo-parameters, including applied load, sliding speed, and sliding distance, on the dry sliding wear of the composites was examined using L27 orthogonal array. Microstructural analysis and hardness data revealed a uniform distribution of SiC particles within the copper matrix, with composite hardness increasing as SiC loading increased. The greatest influence on wear loss was the wt. % of SiC (29.33 %), followed by sliding speed (27.53 %) and applied load (20.66 %), while sliding distance had the least impact (19.32 %). Increasing SiC from 5 to 10 wt. % reduced wear loss by 15.73 %, whereas an increase from 10 to 15 wt. % led to a 9.33 % reduction. The results obtained in this study using the Taguchi technique are valuable for enhancing and further exploring the friction and wear behavior of hybrid particulate-reinforced copper matrix composites.